JONGKE FESTIVAL MARKETPLACE AT LAWEYAN, SOLO - Cynthia Garetta, Agnes
Jongke Festival Market in Laweyan, Solo, a traditional market as shopping areas and tourist Solo selling genuine products both in the fields of arts, crafts, and culinary integrated, which unites the whole arts/ crafts/ products and typical cuisine from around the City Solo and its surroundings in an area with keeping the concept of shopping 'traditional Javanese-style'. The underlying idea is the desire to organize small entrepreneurs, medium enterprises and local artists of Solo in a managed area to maintain the continuity of their businesses and market their local products for making it easier for local communities, local tourists and foreigners alike to get to know the art, culture, and Solo typical culinary tastes. Local commodity market is the basis of festival market design include antique bicycles, wood carving, ceramics, batik, and culinary of Solo. The concept of the festival market space formed by clusters according merchandise group commodity cin order to be easier for visitors to have the orientation when shopping and sightseeing. In addition plazas formed also motivated by the city of Solo which has a habit of holding regular events such as mini concerts, cultural festivals, and carnivals batik solo. Festival Market design taking concepts that fit the local context of Java either of the concept of space, the concept of the building, as well as the concept of mass placement. The concept of space pavilion at the customs house in Central Java embodied in the concept of lobby-hall and stalls that have building concept stage, while the concept of the building with a shingle roof material and large roof shape design characterizes in this festival market. Besides the spread placement mass but remain united with plazas make users easy to determine the orientation of the market.